The joint effects of inflammation and renal function status on in-hospital outcomes in patients with acute ischemic stroke treated with intravenous thrombolysis - Zhichao Huang; Xiaoyue Zhu; Xiuman Xu; Yi Wang; Yafang Zhu; Dongqin Chen; Yongjun Cao; Xia Zhang (BMC Neurology)
Abstract Objective We aimed to determine the predictive value of renal function status [estimating glomerular filtration rate (eGFR)] in conjunction with inflammatory biomarkers [white blood cell(WBC) and C-reactive protein (CRP)] for in-hospital outcomes in acute ischemic stroke (AIS) patients treated with intravenous thrombolysis (IVT). Methods We retrospectively screened a total of 409 AIS patients treated with IVT. The study participants were classified into two groups according to post-stroke pneumonia or functional outcome. They were divided into four groups according to the cut-offs of inflammatory biomarkers and eGFR by receiver operating characteristics(ROC) curves for two outcomes of post-stroke pneumonia and functional status: WBC↓/eGFR↑, WBC↓/eGFR↓, WBC↑/eGFR↑, and WBC↑/eGFR↓for post-stroke pneumonia; and CRP↓/eGFR↑, CRP↓/eGFR↓, CRP↑/eGFR↑, and CRP↑/eGFR↓for functional outcome. Logistic regression models were used to calculate the odds ratios (ORs) and 95% confidence intervals (CIs) of post-stroke pneumonia or at-discharge functional outcome, using the WBC↓/eGFR↑group or CRP↓/eGFR↑group as the reference. The Net Reclassification Index (NRI) and the Integrated Discrimination Improvement (IDI) were calculated to analyze the combined predictive value. Results Compared with patients in WBC↓/eGFR↑group, those in WBC↑/eGFR↑group had increased risk of post-stroke pneumonia (OR 5.15, 95% CI 1.67–15.87) and poor functional outcome (OR 5.95, 95% CI 2.25–15.74). Furthermore, patients in WBC↑/ eGFR↓group had the highest risk of clinical outcomes (all P value for trend < 0.001), the multivariable-adjusted ORs (95% CIs) were 7.04 (2.42–20.46) for post-stroke pneumonia and 8.64 (3.30–22.65) for poor functional outcome. The addition of WBC and eGFR to the basic model significantly improved risk prediction for post-stroke pneumonia (category-free NRI 69.0%, 95% CI 47.3%–90.7%; IDI 5.4%, 95% CI 2.6%–8.3%) and functional outcome (category-free NRI 59.4%, 95% CI 39.2%–79.9%; IDI 5.3%, 95% CI 2.9%–7.8%). Similarly, when we added CRP and eGFR to the basic model with conventional risk factors, the risk discrimination and prediction for post-stroke pneumonia and functional outcome was also significantly improved. Conclusion Combining renal function status and inflammatory biomarkers within 4.5 h after onset could better predict in-hospital outcomes of AIS patients with IVT.